2015
DOI: 10.1039/c5cp05293a
|View full text |Cite
|
Sign up to set email alerts
|

The role of Jahn–Teller distortion in insulator to semiconductor phase transition in organic–inorganic hybrid compound (p-chloroanilinium)2CuCl4at high pressure

Abstract: (p-Chloroanilinium)2CuCl4(C2H14Cl6CuN2) is from an important family of organic-inorganic layered hybrid compounds which can be a possible candidate for multiferroicity. In situ high pressure FTIR, Raman and resistivity measurements on this compound indicate the weakening of Jahn-Teller distortion and the consequent removal of puckering of the CuCl6(4-) octahedra within the layer. These effects trigger insulator to semiconductor phase transition along with a change in the sample colour from yellow to dark red. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…the change of color upon pressure and temperature variation, respectively. 5,[7][8][9][10][11][12][13][14][15] Their piezochromism is explained by the tilting of the octahedra and reduction of the Jahn-Teller distortion by compressing the long Cu-Cl bond. 7,8 Thermochromism often involves the change in coordination geometry from (nearly) square-planar CuCl 4 2À at low temperature to a distorted tetrahedron at higher temperatures, due to the decreased strength of the hydrogen bonding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…the change of color upon pressure and temperature variation, respectively. 5,[7][8][9][10][11][12][13][14][15] Their piezochromism is explained by the tilting of the octahedra and reduction of the Jahn-Teller distortion by compressing the long Cu-Cl bond. 7,8 Thermochromism often involves the change in coordination geometry from (nearly) square-planar CuCl 4 2À at low temperature to a distorted tetrahedron at higher temperatures, due to the decreased strength of the hydrogen bonding.…”
Section: Introductionmentioning
confidence: 99%
“…5,[7][8][9][10][11][12][13][14][15] Their piezochromism is explained by the tilting of the octahedra and reduction of the Jahn-Teller distortion by compressing the long Cu-Cl bond. 7,8 Thermochromism often involves the change in coordination geometry from (nearly) square-planar CuCl 4 2À at low temperature to a distorted tetrahedron at higher temperatures, due to the decreased strength of the hydrogen bonding. 5,9,10,12,15 Riley et al found that the color change in the thermochromic bis(piperazinium) tetrachlorocuprate could also be induced by laser illumination, but could not establish whether this was really caused by photoexcitation (photochromism) or by local heating due to the laser light.…”
Section: Introductionmentioning
confidence: 99%
“…It can lead to crystal-to-crystal changes or could lead to amorphization. There are studies where we have seen insulator to metal transitions and also piezochromic behaviour at high pressure 8 . Specially, with the pressure limits being pushed to terapascals 51 with the help of the small DAC in the lab and with better and better diagnostic equipment we can expect to see major advances in the field of high pressure science.…”
Section: Discussionmentioning
confidence: 99%
“…So in the former case when the repulsive forces become large due to increased overlap of outermost orbitals, the atoms in the system try to lower the free energy by rearranging themselves. This may lead to different kinds of phase transitions and the new phases could be manifested with different interesting properties 8 . Even on lowering of temperature we can encounter phase transitions involving structural changes or simply changes in properties of the system, but, the effects are far less pronounced than observed at high pressure.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the thermochromic behavior of hybrid structures is usually caused by lattice distortion, lattice expansion, or ion rearrangement. [23][24][25] The introduction of some typical transition metal ligands will achieve fascinating thermochromatism, such as in typical thermochromic transition metal complexes based on Cu 2+ , Ni 2+ , Co 2+ , and Fe 2+ ligands, which can serve as a promising green technology. [26][27][28] However, among the 'control knobs', temperature, a basic variable in materials science, has been relatively little-researched in organic-inorganic hybrid halides.…”
Section: Introductionmentioning
confidence: 99%